Perception of Illness in Patients Undergoing Hemodialysis: A Qualitative Study - M Saeedi; R Ghafarzadeghan; D Hekmatpou (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: End- stage renal disease and hemodialysis dependence affect all aspect of patients' life and bring them different experiences. The aim of the present study is to explore the perception of illness in hemodialysis patients. Materials & Methods: This qualitative research was conducted, using inductive and conventional qualitative content analysis approach. Data were collected through semi-structured interview with 21 patients in the hemodialysis ward of Valiasr hospital, selected by purposeful sampling. All interviews were performed by one researcher within two months. Each interview lasted 40 minutes. The data were analyzed along with data collection process. Results: During the data analysis process, five categories were extracted, i.e. disabling complications of disease, hopelessness, life dissatisfaction, the sense of dependence, and turbulent thoughts. "Helplessness caused by the disease" was emerged as the theme of this research. Conclusion: The findings of this research showed that hemodialysis patients often encounter unpleasant experiences, leading to helplessness and a decreased quality and hope of life. Therefore, the physicians and nurses of hemodialysis ward should pay more attention to the problems of these patients.